Current status of infrapopliteal artery stenting in patients with critical limb ischemia - Marc Bosiers (Jornal Vascular Brasileiro, 2008)
Due to the fear that early thrombosis and late luminal loss resulting from intimal hyperplasia might impede sustained patency of small-caliber arteries, such as those of the infrapopliteal bed, stent implantation in below-knee vessels remains controversial and is generally reserved for cases with a suboptimal outcome after percutaneous transluminal angioplasty (i.e. > 50% residual stenosis, flow-limiting dissection). Although evidence starts to build, favoring the use of stenting in the tibial area, results of well-conducted randomized controlled trials have to be awaited to change this strategy. Because of diameter similarities with coronary arteries, the first stents applied in the infrapopliteal vessels were all coronary devices. Once the feasibility of the stenting approach with these coronary products was shown, device manufacturers started to develop a dedicated infrapopliteal product range. To date, a broad spectrum of stent types has been used and investigated for the given indication. This article overviews the available literature and results of different balloon-expandable (bare metal, passive coated, drug eluting), self-expanding and absorbable stent types available for below-the-knee application and gives recommendations for future device technology advancements.